Assessing the Effectiveness of Differentiated Instruction Strategies in Diverse Classrooms - Ira Pasira (Journal of Education Review Provision, 2022)
The study's primary objective is to learn how well differentiated techniques perform in inclusive classroom settings. Formative evaluation was used in this study. This entails checking in on students' progress during the unit of study to make any necessary adjustments to their education. The research demonstrates that kids have varied learning styles, interests, and demands, and it aims to build a learning environment that caters to the requirements of all students. Differentiating education in inclusive classrooms can be accomplished in a number of ways, such as through the use of flexible grouping, tiered assignments, modifications to the learning environment, and the application of multiple pedagogical approaches.